Notes on the genera Antinia Pascoe, 1871 and Dermatodina Faust, 1895 with description of D. boroveci sp. nov. from Thailand (Coleoptera: Curculionidae: Entiminae) - Kania, Jarosław; Piwnik, Agata (Zootaxa, 2017)
The generic status of Dermatodina Faust, 1895 is restored and characters distinguishing this genus from Antinia Pascoe, 1871 are discussed. A new species, Dermatodina boroveci sp. nov., is described from Thailand. A checklist of species placed within the two genera is provided.